2008
DOI: 10.1371/journal.pone.0001423
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Risk for HIV-1 Infection in Adolescents and Young Adults in São Paulo, Brazil

Abstract: BackgroundRecent studies have sought to describe HIV infection and transmission characteristics around the world. Identification of early HIV-1 infection is essential to proper surveillance and description of regional transmission trends. In this study we compare people recently infected (RI) with HIV-1, as defined by Serologic Testing Algorithm for Recent HIV Seroconversion (STARHS), to those with chronic infection.Methodology/Principal FindingsSubjects were identified from 2002–2004 at four testing sites in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the earlier study, HIV seropositivity was also positively associated with early sexual initiation (<12 years old) and unprotected sexual intercourse with a male partner (whether the respondent was male or female). Second, Bassichetto et al showed that in Sao Paulo 78.9% of CTA users testing positive and aged 14-25 were single, and that sexual exposure was responsible for 98.7% of cases [21]. Although 40% of seropositive subjects were PWID, blood-to-blood transmission was not thought to be responsible for any infections in this sample.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In the earlier study, HIV seropositivity was also positively associated with early sexual initiation (<12 years old) and unprotected sexual intercourse with a male partner (whether the respondent was male or female). Second, Bassichetto et al showed that in Sao Paulo 78.9% of CTA users testing positive and aged 14-25 were single, and that sexual exposure was responsible for 98.7% of cases [21]. Although 40% of seropositive subjects were PWID, blood-to-blood transmission was not thought to be responsible for any infections in this sample.…”
Section: Resultsmentioning
confidence: 77%
“…Women attending a CTA in Rio de Janeiro in 2001 had an HIV prevalence of 6.8% amongst 14-19 year olds and 9.3% amongst 20-24 year olds [20]. Between 2002 and 2004, Bassichetto et al found that among HIV-positive adolescents and young adults, 28.6% of 14-19 year olds and 24.4% of 20-24 year olds were diagnosed as recently infected based on STARHS, and that these proportions were higher than in older age groups [21]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were selected from a cohort designed to recruit recently HIV-1infected people in 2002 in São Paulo, Brazil [26,27]. All procedures adopted in this study were performed according to the terms agreed by the Institutional Review Board from the Hospital das Clínicas, University of São Paulo (CAPPesq, Research Projects Ethics Committee, São Paulo, Brazil).…”
Section: Patientsmentioning
confidence: 99%
“…In Latin America, the infection remains generally stable and almost half of the people living with HIV are women. In the last decade there has been an increase in the incidence of HIV/AIDS among young women and a large proportion of infections can be attributed to the behavior of their male sexual partners 1,16,32 . This factor is even more evident where the heterosexual relationship is the dominant manner of HIV transmission 25,32 .…”
Section: Introductionmentioning
confidence: 99%